Internationalizing Teachers’ Preparedness: The Missing Link in Ontario’s Strategy for K–12 International Education? - Trilokekar, Roopa; El-Masri, Amira (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
While the need to internationalize teacher education is recognized by scholars and practitioners, little attention is paid to the role of policies and policy makers in supporting this endeavour. This study focuses on the enactment of Ontario’s K–12 international education strategy by examining four key policy actors—the Ontario Ministry of Education, the Ontario College of Teachers, school boards, and Faculties of Education—and their role in realizing (or not) the internationalization of teachers’ preparedness. A siloed approach, conflict in policy messaging, overlooked policy alignments, and weak policy framing result in weakening the relevance and importance of the internationalization of teachers’ preparedness to meet Ontario’s objectives of inclusivity, diversity, and equity in its public education. Keywords: internationalization, teacher education, K–12 international education, policy enactment